Investigation of Physicochemical Properties and Characterization of Leaf Stalk Fibres Extracted from the Caribbean Royal Palm Tree - S. V. Gurupranes; L. Natrayan; S. Kaliappan; Praveen Bhai Patel; S. Sekar; P. Jayaraman; C. K. Arvinda Pandian; E. S. Esakkiraj (International Journal of Chemical Engineering)
Synthetic fibres (SF) are replaced by natural fibres (NF) and are utilized as polymer reinforcement owing to their eco-friendliness. The composite has been introduced in the current development by employing NF as reinforcement and stuffing in the polymer matrix (PM). The advantages of using natural resources are being eco-friendly, having plentiful natural availability, higher strength, lower cost, and a simple extrication process. When heated to a specific temperature, certain synthetic products create noxious materials. Therefore, replacing these synthetic substances with natural substances has greater advantages for the environment. In this study, a novel NF extricated from the Caribbean royal palm (CRP) along with its features is determined to replace the harmful SF effectively. The CRP’s leaf stalks, termed CRP leaf stalk fibres (CRPLSFs), are extricated and categorized by (i) thermogravimetric analysis (TGA), (ii) scanning electron microscopy (SEM), (iii) Fourier-transform infrared (FT-IR) spectroscopy, (iv) physical-chemical analysis, (v) X-ray diffraction (XRD), and (vi) tensile test (TT). The physical-chemical characteristics of CRPLSFs, cellulose content (CC), tensile strength (TS), density, and hemicelluloses correlate with other NF characteristics. The CRPLSFs’ chemical components include hemicelluloses (14.52%), lignin (9.15%), and cellulose (61.67%). The TGA shows that the CRPLSFs are thermally stabilized up to 326°C. The XRD proved that the CRPLSFs are enriched with a cellulose fraction comprising a crystallinity index (CI) of 30.27%. The outcomes recommended that the biodegradable coconut peduncle leaf stalk fibres (CPLSF) could be exploited as possible reinforcement in the PM composite structure and can be engaged in making composites.